Introversion and Social Engagement: Scale Validation, Their Interaction, and Positive Association With Self-Esteem - Tuovinen, Sanna; Tang, Xin; Salmela-Aro, Katariina (Frontiers in Psychology, 2020)
Learning through social interaction has been documented widely; however, how introverted people are socially engaged in learning is largely unknown. The aim of this study was, first, to examine the reliability and validity of the social engagement scale among students at Finnish comprehensive schools. Then we aimed to examine the interaction effect of introversion and social engagement on self-esteem, schoolwork engagement and school burnout. Based on a sample of 862 ninth grade students in Finland, we found that two-factor model best fitted the social engagement scale (i.e., social engagement and social disengagement). Further, we found that introverts with high social engagement have higher self-esteem than introverts with low social engagement. Our results implied that introverts should be given extra support when they encounter group works in school.